The Blue Glow from the Back Row: The Impact of New Technologies on the Adolescent Experience of Live Theatre - Richardson, John M (University of Ottawa (Canada), 2010)
This article considers the impact of new technologies on the adolescent experience of live, literary theatre. Drawing together the work of theorists in literacies, new technologies and audience studies, together with brain research, and the results of a focus group of four secondary students who have seen four plays at Canada's National Arts Centre, it examines the consequences of young people's immersion in digital culture and the new mindset that often results. The expectation of instant access to data, inter-connectivity, stimulation and control can make it difficult for adolescents to decode the metaphorical aspects of a theatrical performance. The article concludes that language arts and dramatic arts educators have a key role in teaching students how to decode---and therefore enjoy and appreciate---a play. Keywords: theatre, new technologies, new literacies, school audiences, youth audiences, discourse, space, audience studies
Keywords: Education, Performing Arts.; Theater.; Multimedia Communications.